Penguatan Kemampuan Berpikir Kritis Sebagai Pondasi Literasi Digital di Pendidikan Sekolah Dasar - Rose Kusumaning Ratri (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2025)
The development of digital technology has transformed the processes of information production and distribution. The condition must be addressed by the education sector as both a challenge and an opportunity in preparing students to face the realities of life in the digital age. Learners are required to possess digital literacy skills as part of essential competencies. Therefore, critical thinking as the foundation of digital literacy, needs to be taught from the elementary school level. The study aims to examine the concept of critical thinking and effective pedagogical strategies to foster this ability in the elementary school learning environment. The research method employed is a literature study with a descriptive qualitative approach. The findings indicate that critical thinking is a competency that can be systematically taught and developed through active student engagement in inquiry-based learning, problem-based learning, and cooperative learning. The study concludes that strengthening critical thinking skills in elementary school students constitutes a strategic step toward building comprehensive digital literacy.